Unlocking the optimum supercapacitance of Co3O4 by reducing the Co valence state via Mn doping. (September 2021) - Liu, Shujie; Nan, Haoshan; Li, Lin; Qin, Tingting; Cai, Lin; Zhang, Wei; Zheng, Weitao
Abstract: Trivalent Co in Co3 O4 electrodes cannot efficiently contribute to a high capacitance based on the redox reaction between Co3 O4 and CoOOH in alkaline electrolytes; In contrast, increasing the content of divalent Co can enhance the capacitance. Herein, we demonstrate that doping Mn into Co3 O4 increased the content of divalent Co increases, which was accompanied by induced lattice distortion and the formation of oxygen defects. As a result, our designed Mn-doped Co3 O4 electrodes were unlocked with optimum electrochemical storage performance. For instance, the (Mn0.75 Co2.25 O4 ) electrode achieved a high specific capacity of 164.44 mAh/g and outstanding cyclic stability with 96% capacity retention at a current density of 4 A/g after 3000 cycles. Graphical Abstract: ga1